Weather pattern definitions for India and their daily historical classifications (1979 to 2016) - Neal, Robert; Robbins, Joanne; Dankers, Rutger; Mitra, Ashis; Jayakumar, Amal; Rajagopal, E N; Adamson, George (Supplement to: Neal, R et al. (2020): Deriving optimal weather pattern definitions for the representation of precipitation variability over India. International Journal of Climatology, 40(1), 342-360, https://doi.org/10.1002/joc.6215, 2019)
Mean u- and v- component wind fields at 850-hPa are provided over India for a set of 30 objectively derived weather patterns, which were generated by k-means clustering of daily (1200 UTC) reanalysis fields from ERA-interim between 1979 and 2016. The weather patterns are defined on a 1 x 1 degree resolution grid, which covers the area from 62 degrees west to 98 degrees west and 2 degrees north to 37 degrees north. The boundary coordinates represent the central positions of the outer grid points. Also provided are daily historical weather pattern classifications covering the same period, where the observed weather patterns are valid at 1200 UTC daily. The observed weather pattern on each day is given as a number from 1 to 30, which matches up to the weather patterns defined in the gridded data set. Column 1 of this dataset gives the date and column 2 of this dataset gives the observed weather pattern classification. Both datasets were generated as part of the LANDSLIP (Landslide multi-hazard risk assessment, preparedness and early warning in South Asia integrating meteorology, landscape and society) project which had two UK grant funders: NERC and DFID (Grant numbers: NE/P000681/1 and NE/P000649/1) under the programme SHEAR. This work and some of its contributors (Robert Neal, Joanne Robbins and Rutger Dankers) were also supported by the Met Office Weather and Climate Science for Service Partnership (WCSSP) India Programme as part of the Newton-Bhabha Fund. More information on how these data were created and their suggested use in future research is provided in the associated paper published in the International Journal of Climatology.
Keywords: cluster analysis; forecasts; India; Monsoon; Weather patterns